A new oxygen-rich and poly-nitrogen energetic complex: synthesis, properties of high energy materials and catalytic decomposition of ammonium perchlorate. Issue 7 (30th April 2021) - Li, Bing; Song, Huan; Wu, Huanping; Wang, Jiakai; Tian, Xiaoyan; Ma, Xiaoxia
Abstract: Preparing green materials with excellent performance based on coordination chemistry is a challenge. In the present work, a new energetic complex, [Co(Hatzc)2 (H2 O)2 ] · 2H2 O (1 ) (H2 atzc = 3-carboxyl-5-amino-1, 2, 4-triazole), was synthesized by the diffusion method and characterized by X-ray single-crystal diffraction, elemental analysis, infrared spectral analysis, and thermogravimetric analysis. The structural analyses illustrate that 1 exhibits a 0-D motif, linked by hydrogen-bonding interactions to give a 3-D supramolecular architecture. 1 shows good thermal stability ( T dec =283 °C), low sensitivity (IS > 40J, FS > 360N), prominent detonation velocity (10.18 km s −1 ), and detonation pressure (44.99 Gp). The heat of detonation of 1 (4.109 kcal g −1 ) is higher than most classical energetic complexes as shown by density functional theory (DFT). In addition, 1 shows good catalytic activity toward AP (ammonium perchlorate) decomposition by thermodynamics and dynamic analysis, which indicates 1 is a potential energetic candidate in the solid propellant field. Graphical Abstract: